Understanding factors influencing wheat productivity in Ethiopian highlands - Kihara, Job Maguta; Gurmessa, Biyensa Dubiwak; Tamene, Lulseged D.; Amede, Tilahun; Sommer, Rolf (Cambridge University Press, 2022)
Increasing yields in farmer fields is a priority to address increasing food demands. The study was conducted within four wheat-growing areas in Ethiopia: Debre Birhan, Hosaina, Sinana and Maychew. The objectives were to identify (1) best-bet soil fertility management options based on agronomic performance and economic evaluation and (2) key yield-reducing factors in farmer fields based on an agronomic survey among 55 participating farmers. Two types of on-farm experiments were conducted: researcher-managed trials that tested combinations of nutrients, including micronutrients, organic resources or both over two cropping seasons and farmer-managed trials comparing ‘improved practice’ against ‘farmer’s practice’. Fertilizer treatment affected wheat productivity in Debre Birhan (p < 0.01), a site limited in sulphur. Here, full NPK increased yields over the control (p < 0.05), whereas a combination of NPK and manure was better than the application of manure as the only source of added nutrients (p < 0.05). Applying half the recommended NPK with micronutrients and manure achieved similar yields as the full fertilizer treatment. In Hosaina, treatment had no significant effect on wheat productivity, although a combination of NPK and zinc resulted in an additional 26–57% yield relative to the other treatments. In Maychew, a significant treatment effect (p < 0.05) was observed. Here, the treatment with lower rates of nitrogen and phosphorous had lower yields than the full NPK treatment. A significant effect of plant densities on on-farm productivity was also observed. We conclude that although nutrient management including use of micronutrients is important in specific cases, investments to optimize plant densities have a huge potential to increase food productivity.